Canto coral em projetos sociais: trajetória de uma educadora em Santa Maria - RS - Junges, Fernanda (2013)
This dissertation named entitled: Choral in social projects: the story of a teacher in Santa Maria - RS, is developing in the Post-Graduate Education, of Federal University of Santa Maria, in the Research Line Education and Arts (4 LP.) It presents the trajectory formation of a bachelor teacher and his work as regent/educator in Santa Marta Social Marist Center. Approaches the challenges of teaching for teachers with bachelor's degree in education, talks about music education in social projects through a methodology of oral history and discusses self-training through the narrative. In the process of analysis of the trajectory formative Neida, develops a dialogue with several authors, mainly Kater (2004) and Josso (2010). In data analysis, discusses the speech of the interviewee with respect to recall its history, seeking to oppose the concept of humanizing musical education brought by Kater. This research aims to contribute to the discussions on the self-training of music teachers, specifically with regard to choral singing in social projects.